Electronic cigarette use among adolescents in 17 European study sites: findings from the Global Youth Tobacco Survey. (25th October 2021) - Tarasenko, Yelena; Ciobanu, Angela; Fayokun, Ranti; Lebedeva, Elizaveta; Commar, Alison; Mauer-Stender, Kristina
Abstract: Background: As new findings on public health implications of electronic cigarette (e-cigarette) use emerge, its surveillance remains of utmost importance. This study examined the latest state of e-cigarette use in youth in 17 European study sites (i.e. 16 countries and the Federation of Bosnia and Herzegovina) using the Global Youth Tobacco Survey (GYTS). Methods: This was an observational study. Cross-sectional data on students aged 11–17 years from the latest available GYTS round completed in 17 study sites were used to estimate crude and adjusted prevalence of e-cigarette use by sex and pocket money. Panel GYTS data from five countries were used for the trend analyses. All analyses were weighted to account for the survey design and non-response. Results: Compared to 2014, the age-adjusted prevalence of e-cigarette use more than doubled in Georgia and Italy, and nearly doubled in Latvia. Significantly more male than female students aged 11–17 years reported use of e-cigarettes, with little to no confounding by age, grade and pocket money across countries. Youth with medium or higher amount of pocket money was 20–200% more likely to use e-cigarettes than those with fewer to no pocket money in 14 study sites. Discussion: As e-cigarette use is becoming widespread throughout the world, there is variation in use among and between countries. Expanded and consistent surveillance of e-cigarette use by all World Health Organization member states is essential to generate data on the extent and correlates of youth e-cigarette use for evidence-based planning and evaluation of the electronic nicotine delivery systems and electronic non-nicotine delivery systems national and global control programmes.